PENGARUH GAME EDUCAPLAY PADA KEMAMPUAN KEAKSARAAN ANAK USIA 4-5 TAHUN DI TK PEMBINA 1 KOTA JAMBI - Sukamto, Siska Noviana; Destrinelli; Asih Nur Ismiatun (STKIP Subang, 2026)
This study aims to determine the effect of using the Educaplay game on the literacy skills of children aged 4–5 years at TK Negeri Pembina 1 Kota Jambi. The background of this research is based on the low level of early literacy skills among children, as shown in initial observations, which indicates the need for more engaging and interactive learning media. This study employed a quantitative approach with a quasi-experimental design using a one-group pretest-posttest model. The participants consisted of 12 children aged 4–5 years selected through a saturated sampling technique. The research instruments included pretest and posttest assessments as well as observation sheets consisting of six indicators of literacy skills, such as letter recognition, vocabulary understanding, word formation, and matching images with words. Data analysis techniques included normality testing, the Wilcoxon Signed Rank Test, and effect size calculation. The results showed that the mean pretest score was 12.58 with a percentage of 69.91%, while the mean posttest score increased to 18.75 with a percentage of 78.13%. The Wilcoxon test results indicated a significance value of 0.002 (< 0.05), meaning there was a statistically significant difference between pretest and posttest results. Furthermore, the effect size value of Cohen’s d = 2.72 indicated a very large effect. These findings demonstrate that the use of the Educaplay game has a significant and strong effect on improving early literacy skills in children aged 4–5 years. The game-based learning approach enhances motivation, engagement, and active participation, making it more effective than conventional learning methods in early childhood education.